Sensitivitas Kelayakan Investasi Rumah Susun di Kabupaten Sidoarjo - Eddy Priyanto; Tri Yuliyanti (Wahana Teknik, 2021)
The development of an apartment as an investment that involves a large amount of funds with the hope of getting a profit in the long term, often has a big impact on the survival of the company. To anticipate the trend of changes that occur, it is necessary to do a sensitivity analysis. The goal to be achieved is to find out what will happen to the results of the project analysis if there is a change. Changes in cost and price increases will affect the amount of Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), Profitability Index (PI) and the initial risk analysis. This study uses a quantitative approach through empirical calculations in its analysis. The conclusion is that the NPV that uses a 30% occupancy risk level of depreciation is supported by an 80% increase in income and a reduced expenditure by 50%, so the Pucang Flat Phase II development plan is feasible. This is clarified by the result of NPV3 = IDR 3,409,790,045.00 because it is greater than zero. The payback period obtained is lower than the specified limit, namely the PP value = 24.67 years < 25 years. And for the results of the IRR calculation analysis, the results obtained are IRR = 14.7% > 14%. Then from the analysis of the calculation of the Profitability Index (PI) method, it was obtained a value of 1.23 which means that the Pucang Flat Phase II development is feasible to be carried out. However, when viewed from the level of risk based on the value of NPV1 = IDR -16,909,705,762.00, NPV2 = IDR -14,529,162.110.00 and NPV3 = IDR 3,409,790,045.00 which have probabilities of 0.1 and 0.2 and 0.7, it is explained that the investment in the development of Pucang Flat Phase II is very risky to implement. Overall, from the results of the analysis for the feasibility of investing in the development of Pucang Flat Phase II in Sidoarjo Regency, it is feasible to carry out. Keywords: feasibility, flat, investment, sensitivity, sidoarjo